Islamic occultism and the museum - Leoni, F (Intellect, 2018)
The exhibition Power and Protection: Islamic Art and the Supernatural, held at the Ashmolean Museum, Oxford, between 20 October 2016 and 15 January 2017, provided the opportunity to reconsider some of the parameters employed in largescale Islamic art exhibitions. The subject of the show – select divinatory and amuletic practices, itself a break from more conventional themes – was explored by adopting a more inclusive and critical approach, drawing evidence from a wide social spectrum and transcending classifications of ‘ethnographic material’ and ‘fine art’. Attention was also given to daily practice, creating a fresh vantage point to reflect on the role and forms of devotion and broader notions of belief. While presenting practices and evidence that many might deem marginal (and that have certainly been marginalized over time), the exhibition ultimately offered a new analytical lens to challenge hierarchies of higher and lower culture, as well as sanctioned versus heterodox religious practices that continue to structure museum presentations and inform public perception of Islamic culture. By exploring the difficulties, achievements, and shortcomings of the project, and by incorporating insights from audience evaluations and impact questionnaires, this article reflects on the range of factors that shape today’s presentations of Islamic art and culture in the museum, as well as on the unprecedented challenges faced by specialists of Islam in western institutions at this critical historical moment. Furthermore, by considering the exhibition in the context of the current, revitalized museological interest in religions, it offers a contribution to the broader debate about religious objects in secular institutions and the need to reconcile multiple views and expectations.